Girls in Football, Boys in Dance. Stereotypization Processes in Socialization of Young Sportsmen and Sportswomen - Jakubowska, Honorata; Byczkowska-Owczarek, Dominika (Qualitative Sociology Review, 2018)
The article at hand presents and discusses the issue of gender stereotypization strategies during the socialization process of children practicing atypical gender sports, which is perceived as inappropriate to their gender. The outcomes of two qualitative studies among girls playing football and boys practicing ballroom dancing focus on various types of social influence of their families, coaches, and peers. The importance of parents’ role in reproducing or challenging stereotypical gender roles is outlined in the text. The strategies to which the children participating in atypical gender sports are subjected to include: stereotypization, destereotypization, apparent destereotyping, and hidden stereotyping. The benefits of participating in atypical gender sports are also discussed, particularly in terms of social and psychological profits.